Explaining the Telepractice Process of Stuttering in Preschool Children: A Grounded Theory Study - Mohammad Hosein Rohani Ravari; Akbar Darouie; Abbas Ebadi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Stuttering is one of the speech disorders that appears in childhood. Many studies emphasize early interventions for its treatment. Circumstances such as a lack of therapists and the COVID-19 pandemic have limited the access to face-to-face therapy. Studies show some problems with this type of treatment. A detailed understanding of these problems in a cultural context can help increase the quality of providing telepractice. This study was conducted to discover the telepractice treatment of stuttering in preschool children. Materials & Methods This qualitative study was conducted in Iran from November 2020 to February 2022 using the grounded theory method. In this study, in-depth, free, and individual interviews were conducted with 9 therapists and 5 parents of children who stutter. The data were analyzed using the Corbin and Strauss method, version 2015. Results After analyzing the data of this study, 6 main categories, 17 subcategories, and 63 primary categories were extracted. The main categories include "hesitation in choosing telepractice", "characteristics of family and clients", "technology and the knowledge to apply it", "therapist skills for telepractice", "payment system for telepractice fees", and "efficiency of telepractice". Conclusion In this study, "efficiency of telepractice" was chosen as the central concept that all participants were concerned about in some way. According to this model, "hesitation in choosing telepractice", "characteristics of family and clients", and "technology and the knowledge to apply it" as the context have effects on the processes that are taking place in relation to the telepractice in preschool children who stutter. These processes include "therapist skills for telepractice" and " payment system for telepractice fees". In the end, all these things increase the efficiency of telepractice.